The Last Days of Tell el-Ghaba. The Egyptian Ceramic Evidence - Lupo, Silvia Alicia (2007)
The Egyptian and imported pottery from the destruction layer L0001 and L1001 are included in this ceramic analysis, with a short morphologic and stylistic description of the vessels, and the comparison with material from other sites of Egypt, the Levant and the Eastern Mediterranean. The destruction layer, which covered the whole excavated area, 1 is a dark, charcoal-rich sediment with oxidation lenses, characteristic of a conflagration layer.2 Abundant ceramic remains, fragmentary and eroded, were recovered.